A thermotropic poly(ether ketone) based on the p-quaterphenyl unit: evidence for a smectic C phase. Issue 1 (28th November 2019) - Oladoyinbo, Fatai O.; Lewis, David F.; Blundell, David J.; Colquhoun, Howard M.
Abstract : A poly(ether ketone) based on the p -quaterphenyl unit shows liquid crystalline character, forming a smectic C phase from the isotropic melt. Abstract : High-temperature polycondensation of 4, 4′-(hexafluoroisopropylidene)diphenol with the homologous series of bis(fluoroaryl)diketones FArCO[Ar] x COArF (Ar = 1, 4-phenylene, x = 1, 2, 3 or 4) affords polyetherketones [–OArC(CF3 )2 ArOArCOAr x COAr–] n . The polymers with x = 1–3 are conventional amorphous thermoplastics, but when x = 4 much more complex and unusual phase behaviour is seen. The thermophysical characteristics of this polymer have been investigated by DSC and by X-ray powder and fibre diffraction. The results are accounted for on the basis that cooling from the isotropic melt (which is present above 375 °C) leads to rapid formation of a smectic-C-type mesophase at around 330 °C, with higher levels of order developing more slowly over a broad temperature range between ca. 300 and 230 °C.